Characterization of the auxiliary activity enzymes Trichoderma reesei TrAA3_2, TrAA9A and Podospora anserina PaAA9E, with potential roles in cellulose modification - Hiltunen, Mimmu (2021)
Sustainably produced fuels and materials will be critical for the survival of our species, but a cost and time efficient production method is yet to be developed. Plant-based waste could be a part of the solution: one of its main components, cellulose, is a starting point for the production of biofuels and chemicals. However, the recalcitrant nature of the main component of plant-based waste, lignocellulose, as well as the enigmatic nature of lignocellulolytic enzymes and their cooperation, has hindered adopting applications on a global scale. The aim of this study was to characterise three fungal enzymes with potential roles in lignocellulose degradation. First, we aimed to characterise the activity and phylogenetic location, as well as build a homology model, of a novel Trichoderma reesei AA3_2 subfamily enzyme (TrAA3_2). Secondly, we aimed to characterise the H2O2 dependency as well as thermal and pH stability of two lytic polysaccharide monooxygenases (TrAA9A and PaAA9E). Thirdly, we aimed to evaluate the effects of TrAA3_2, TrAA9A, and PaAA9E on the hydrolysis of spruce biomass by a cellulase mixture. We found that TrAA3_2 is phylogenetically closest to glucose oxidases but were unable to detect activity with any of the assayed carbohydrate or alcohol substrates. The homology model revealed that the substrate-binding residues of TrAA3_2 differ from those found in two well-characterised oxidative glucose active enzymes, possibly explaining the apparent inactivity for glucose. Furthermore, we found both TrAA9A and PaAA9E to be active with both O2 and H2O2 as a cosubstrate, and to be stable at 40 C and pH 5–7. TrAA9A was found to enhance the hydrolytic efficiency of a cellulase cocktail mimicking commercial lignocellulolytic cocktails. Based on our results, TrAA9A and PaAA9A display both oxidase and peroxidase activity, and may be good candidates for practical applications.